Autentyzm? Autograficzność? Głos w sprawie najmłodszej polskiej prozy - Adamczewska, Izabella (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The article focuses on the analysis of the post-1989 Polish prose of writers born in the late 70’s and early 80’s of the 20th century. They set their works in small, face-to-face communities: peer, regional or work-place. In each case, the nature of the community or communities represented is discussed, with special focus on the specifics of social structure. The young writers reflection on the post transformation everyday life in Poland is based on their own experiences. The paper is concerned on the autobiographical strategies of this fiction, which are discussed mainly in the historical context of the between the wars Polish social novels.